A case report of a primary synovial chondromatosis of temporomandibular joint, producing medial displacement of the articular disc. (11th September 2014) - Droguett, C.; Fumeaux, J.E.; Skármeta, N.P.
Abstract: Synovial chondromatosis in the temporomandibular joint (TMJ) is a rare benign cartilaginous metaplasia characterized by the formation of loose bodies within the synovial joint space. This condition presents a specific triad of semiological characteristics featuring pain, swelling, and limitation of function. We will present a clinical case of a 49 years‐old female patient who presented to the clinica Davila's maxillofacial service with severe functional alterations in her right TMJ. Clinically, the patient had a maximum aperture of 15 mm wide, alteration of mandibular dynamics and preauricular pain. Posterior conducting a complete clinical examination and conclusive magnetic resonance imaging (MRI) findings it was decided to perform surgery on the joint. Articular cavity was exposed through a preauriclar approach, where the joint capsule presented no evident alteration. After opening the capsule, we were able to identify and extract multiple cartilaginous bodies both above and below the disc space. The articular surfaces were in good condition, while the articular disc was shifted to the medial portion of the cavity. The removal of the loose bodies was held the meniscopexy of the articular disc with a small joint anchor. The immediate post‐operative period was uneventful, and the patient did not present any alteration with respect to motor function of facial expression. At the 6‐week control, we recorded an increase in maximum mouth opening of 30 mm and a reduction of the pain. Six months later, we recorded an even wider mouth opening with no signs or evidence of recurrence.